Understanding Personal Motivation between Willingness to Participate in E-sports and Potential Consumption - Zhang, Jiawei (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence